The women of Sta. Rita their role in fishing. - Obaob, Ignacio; Valaquio, Jan Reuell (2002.)
The study was conducted using an interview schedule given to the women of Brgy. Sta. Rita, SanJoaquin aging fifteen to sixty years of age and above. In the interview, the respondents were asked about their socio-demographic profile. What were the activities of women related to fishing and their perception with regard to their activities was also included in the interview., Analyzing the results from the data gathered the researchers found out that most of the respondents were exposed to fishing related activities in an early age and most of them have only reached elementary level, thus, denying them with other alternative livelihood rather than fishing.The activities related to fishing of women of Brgy. Sta. Rita are concentrated to near-shore activities such as: panahid (a near-shore fishing technique in catching fish by using a U-shaped net) and gathering seashells. The activities they perform before fishing trip are asually: preparing the materials for fishing such as sewing the damaged fish nets and making the bundak (a local kind of fish hook made up by nylons and hook which is usually wrap a small bamboo pole). In addition, they also prepare the food and clothes used by their husbands in their fishing trip. The activities of women after the fishing trip is usually selling of the fish catch in the town's public market.
Paper (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Women -- Sta. Rita; Women -- Role in fishing